A service to automate the task assignment process in YAWL - Samanthula, Krishna Nagarjun Reddy (Kansas State University, 2010)
Developing an optimal working environment and managing the of work load in an efficient manner are the major challenges for most businesses today. So, the importance of the workflow and workflow management in an organization is unquestionable. Many organizations use sophisticated systems to organize the workflows. One such workflow system based on a concise and powerful modeling language called “Yet Another Workflow Language” is YAWL. YAWL handles complex data, transformations, integration with organizational resources and Web Service integration. Workflow comprises of three main perspectives: control-flow, data and the resources. In Yawl, the control-flow and the data-flow are tightly coupled within the workflow enactment engine. But the resource perspective is provided by a discrete custom service called Resource Service. Administrative tools are provided using which the administrator has to manually select the resource (referred as participant) which needs to perform a particular task of the workflow. This project aims at developing a service which can automate the assignment of the tasks to the participants by using the Resource service which provides number of interfaces that expose the full functionality of the service. The application of this project with respect to Healthcare domain is presented. Healthcare domain is the one of the most demanding and yet critical business process. Hospitals face increasing pressure to both improve the quality of the services delivered to patients and to reduce costs .Hence there is significant demand on hospitals in regard to how the organization, execution, and monitoring of work processes is performed. Workflow Management Systems like YAWL offers a potential solution as they support processes by managing the flow of work.
Keywords: Workflow; Workflow management system; Resourcing; YAWL; Computer Science (0984)